Effect of feeding maize fiber in wet, dry and silage form with cotton cake supplementation on intake, nutrient utilization and performance in Nellore Brown sheep - Ramana Reddy, Y.; Khan, A.A.; Sharada, P.; Ravi, D.; Prasad, Kodukula V.S.V.; Blümmel, Michael (2016)
Maize fiber was evaluated in wet, dry and silage form with 200 g cotton cake supplementation in growing Nellore Brown ram lambs (24.8±0.96) using six sheep per treatment in a growth-cummetabolism trial of 90 days with collection of feed, leftover, feces and urine samples during the last ten days. Average daily gain (g), nutrient digestibility (OM, CP, NDF, ADF) tended to be higher (P = 0.07 to 0.09) and intake of OM, DOM, CP (gld) and ME (MJ!d) and nitrogen retention were significantly (P = 0. 0002 to 0. 002) higher in lambs when fed maize fiber in silage rather than in wet and dry form. Depending on input such as labor required ensilaging or drying of maize fiber seems an economically more beneficial and from a food security point of view a safer way than feeding wet maize fiber.